2015
DOI: 10.1016/j.bjid.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus laurentii fungaemia in a cervical cancer patient

Abstract: Infections caused by emerging Cryptococcus non-neoformans species are being reported with increasingly frequency. Here, we present a case of fungaemia by Cryptococcus laurentii in a woman receiving aggressive immunosuppressive therapy for cervical neoplasia. Three venous blood samples were aseptically collected on consecutive days and C. laurentii was isolated and identified through phenotypic and molecular methods. After central venous catheter removal and appropriate antifungal therapy, the patient showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Although most human infections and specifically, those related to the CNS are caused by C. gattii / neoformans species complex isolates, less common former Cryptococcus spp. have been reported to cause invasive disease due to P. laurentii and N. albida ( Cheng et al., 2001 ; Averbuch et al., 2002 ; McCurdy and Morrow, 2003 ; Shankar et al., 2006 ; Khawcharoenporn et al., 2007 ; Furman-Kuklinska et al., 2009 ; Gullo et al., 2013 ; Neves et al., 2015 ). A systematic review performed by Londero et al., ( Londero et al., 2019 ) reported 35 cases of deep-seated infections due to P .…”
Section: Discussionmentioning
confidence: 99%
“…Although most human infections and specifically, those related to the CNS are caused by C. gattii / neoformans species complex isolates, less common former Cryptococcus spp. have been reported to cause invasive disease due to P. laurentii and N. albida ( Cheng et al., 2001 ; Averbuch et al., 2002 ; McCurdy and Morrow, 2003 ; Shankar et al., 2006 ; Khawcharoenporn et al., 2007 ; Furman-Kuklinska et al., 2009 ; Gullo et al., 2013 ; Neves et al., 2015 ). A systematic review performed by Londero et al., ( Londero et al., 2019 ) reported 35 cases of deep-seated infections due to P .…”
Section: Discussionmentioning
confidence: 99%
“…Infections caused by these species are still rare, so these species have been the object of study for definitions of treatment and prophylaxis. Some studies have helped gain a better understanding of more effective antifungal therapies or new treatment alternatives [34,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcus gattii / Cryptococcus neoformans species complexes) and environmental saprophytes such as P. laurentii (formerly Cryptococcus laurentii ), which was considered non-pathogenic to humans until recently [4–6]. However, a wide spectrum of infections such as fungaemia, meningitis, peritonitis and disseminated skin infections associated with P. laurentii have been described in recent years [10–14, 32, 33]. Production of melanin is considered a major virulence factor of pathogenic Cryptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Infections caused by these two species, particularly P. laurentii , have increased considerably in recent years, particularly in patients with impaired cell-mediated immunity and prior exposure to antifungal drugs [7, 8]. A wide spectrum of diseases has been attributed to P. laurentii in recent years, including fungaemia, meningitis and meningoencephalitis [10–17]. P. laurentii is considered aheterogeneous group since phylogenetic studies based on sequence analysis of the internal transcribed spacer (ITS) region and D1/D2 domains of rDNA revealed that P. laurentii represents a species complex comprising P. aureus , P. aspenensis , P. terresteris , P. flavescens and P. laurentii [9, 15–17].…”
Section: Introductionmentioning
confidence: 99%